If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(a + b) = 10x + -5 (a * F + b * F) = 10x + -5 (aF + bF) = 10x + -5 Reorder the terms: aF + bF = -5 + 10x Solving aF + bF = -5 + 10x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1bF' to each side of the equation. aF + bF + -1bF = -5 + -1bF + 10x Combine like terms: bF + -1bF = 0 aF + 0 = -5 + -1bF + 10x aF = -5 + -1bF + 10x Divide each side by 'F'. a = -5F-1 + -1b + 10xF-1 Simplifying a = -5F-1 + -1b + 10xF-1
| 6cos(3x)+5=0 | | b=1/4*3.14*x2m | | X^2+y^2+4x+8y+4=0 | | t-3/8=1/4 | | 7x^2+14x-8=0 | | P=x^4+2x^2-8 | | 4sin^2(4x)=2 | | n-1/5=3/5 | | 210=30 | | P(x)=x^4+2x^2-8 | | 16e/9=6e-190 | | c=27n+26 | | 26.50+15x=14.50+.25x | | x/7-4=11 | | 98b^2+98b-16=0 | | lnx+ln(x-2)=ln(x-4) | | (10+2x)=25 | | log(3x)-log(14)=0 | | x-2=-3z+2 | | d/2.5-3.5=1.5 | | 3000=8.121x^2+6.406x+257.8 | | h/3.2-1.6=2.5 | | 7/x^2-5x | | h/7.1-6.5=1.2 | | 22z^4/11z^10 | | b/5-19=11 | | 2/3x-3/8x=-8 | | m/7=42 | | b/1.3-5.4=1.8 | | 1/6(x+18)=1/3x+4 | | 16x^3-24x^2+24x-8=0 | | B/5-1=12 |